ADMINISTRATIVE LEGAL REGIME OF THE EMERGENCY SITUATION - Jalilov Ahmadbek Ikromjon ugli (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The article discusses the classification of administrative-legal regimes, defines the role of an emergency and substantiates the need for their counteraction. Legal regimes as complexes of legal means that contribute to the establishment of more or less stable, sustainable administrative and legal procedures for the functioning of certain objects or the activities of certain subjects.